Use of Magnetic Resonance Direct Thrombus Imaging for the Diagnostic Management of Suspected Thrombosis in Routine Clinical Practice - de Jong, Cindy M.M.; van Dam, Lisette F.; Dronkers, Charlotte E.A.; Eikenboom, Jeroen; den Exter, Paul L.; ter Haar, Sophie N.M.; van Haren, Guido R.; Huisman, Menno V.; van Mens, Thijs E.; Stöger, J. Lauran; Kroft, Lucia J.M.; Klok, Frederikus A. (TH Open, 2024)
Background The noninvasive magnetic resonance direct thrombus imaging (MRDTI) technique can be used to diagnose acute deep vein thrombosis (DVT), without the use of intravenous contrast. MRDTI holds the potential to differentiate between acute and chronic DVT and could be helpful when diagnosing thrombosis is challenging.Objectives Our objective was to evaluate the application of MRDTI in clinical practice, including the frequency and indications of MRDTI scans performed in practice-based conditions, results, impact on treatment decisions, and associated patient outcomes.Methods A retrospective study was performed at the Leiden University Medical Center, the Netherlands. MRDTI scans performed since its implementation in patients aged ≥18 years as part of clinical practice for the diagnostic management of suspected thrombosis were evaluated.Results Between October 2015 and September 2023, 36 patients had undergone MRDTI for the diagnostic evaluation of thrombosis. MRDTI application increased since 2019 (five–eight scans per year). The most common indication was to differentiate between acute and chronic thrombosis, mainly for suspected recurrent ipsilateral DVT after inconclusive compression ultrasonography. In over a third of patients, acute thrombosis was confirmed by MRDTI. MRDTI results determined treatment decisions in all except two patients. One patient had symptomatic thrombosis of the lower extremity within 3 months after an MRDTI of the upper extremity without signs of acute thrombosis (1/23; 4.3%, 95% confidence interval: 0.77–21).Conclusion Over the past 4 years, MRDTI has been used increasingly in our hospital. MRDTI results guided treatment decisions, which confirms the clinical impact and feasibility of its application in daily practice.
Keywords: venous thrombosis; deep vein thrombosis; magnetic resonance imaging; diagnostic imaging; radiology